Pengembangan Model Pelatihan Pengintegrasian Teknologi Informasi dan Komunikasi dalam Pembelajaran Matematika bagi Guru SD - Silalahi, Parulian (JTP - Jurnal Teknologi Pendidikan, 2015)
This study aims to produce training materials on the integration of information and communication technology in the teaching of mathematics. The method employed in the study is research and development. Assessment of experts and individual testing on the training materials generated recommendations for revisions. Accordingly, the results of the assessment can be classi ed in the very good category. The assessment results of small groups were very good. The results of eld trials indicate that trainings have signi cant implication for the increase of the trainees’ ability. Based on the results, it can be concluded that training materials on the integration of information technology and the teaching of mathematics have been tested and can be used in trainings for primary school teachers